The Effect of Work Discipline, Organization Comitment, and Work Stress to Employee Performance on RSUD Sidoarjo: Pengaruh Disiplin Kerja, Komitmen Organisasi, dan Stres Kerja Terhadap Kinerja Pegawai di RSUD Sidoarjo - Rio Sandi Triawan; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2021)
This research means to determine the effect of work discipline, commitment, and work stress on employee performance. The following research is based on the fact that RSUD Sidoarjo is experiencing problems with its human resources. Many employees do not comply with the applicable SOPs at work, resulting in decreased employee performance. Based on the declining performance of employees, it resulted in complaints from RSUD Sidoarjo patients at the Graha Delta Husada Installation.The design of this research carried out in this thesis uses the type of quantitative research. In this study using a non-probability sampling technique with a saturated sample technique of 85 medical workers at the RSUD Sidoarjo, Graha Delta Husada Installation.The results of the study prove that work discipline has a partial positive effect on employee performance, organizational commitment partially positive effect on employee performance, work stress partially negatively affects employee performance.